Satellite communications - Roddy, Dennis (McGraw-Hill, 2006)
Highly regarded for more than a decade as both a teaching text and professional tutorial, this classic guide to satellite communications has been revised, updated, and expanded to cover global wireless applications, digital television, and Internet access via satellite.